Improving Health Care Waste Management in Africa: Action Research on how can Staff of Makerere University Hospital be involved in overcoming their Occupational Hazards? - Kusilika, Caleb (Student's Journal of Health Research Africa, 2021)
Background: Action research is a participatory, democratic process concerned with developing practical knowledge in the pursuit of worthwhile human purposes. In a health care setting, numbers of people go there for prevention, treatment, and care including rehabilitation. All these are vulnerable to the hazardous wastes which are generated within such a setting if not properly managed. Health care settings become more detrimental places where diseases can be transmitted and pollutants to the natural environment thus becoming harmful to the whole community at large. The research is aimed at creating both staff and clients with a conducive environment to work and live in with reduced chances of morbidity, injury, or harm occurring secondary to poor waste management. Methodology: This study set out to identify the health-related challenges faced by Makerere University Hospital, determine the causes of poor health care wastes management, and setting up the appropriate mitigating solutions. Data was generated using interviews for primary data and documents focused on group discussions for secondary data. Multi-voting and nominal techniques were used to identify the priority health problem. A problem and solution tree were used to provide an overview of all the known causes and effects to the identified problem and their solutions. Results: Most of the respondents were women 26(52%) and men were 24(48%). These were Classified into staff with clinical background 32(64%) and non-clinical staff 18(36%). Several problems were listed among which included a need to have an administrator who is medical personnel. Conclusion and recommendations: Poor health care waste management was the most pressing problem in Makerere University Hospital. Collaborating with the hospital community to address the poor waste management approaches, helped to improve the waste segregation, storage, transportation, and disposal in conjunction with strengthening staff empowerment that both contribute to good health living in such health settings.